An Expeditious Benzannulation Reaction of Indol‐3‐yl‐but‐3‐yn‐2‐ols to Substituted 2‐Iodocarbazoles via Domino 5‐endo Spirocyclization/Selective Vinyl Shift and Aromatization. Issue 41 (28th October 2019) - Yaragorla, Srinivasarao; Dada, Ravikrishna; Bag, Debojyoti
Abstract : Regioselective benzannulation reaction of indol‐3‐yl‐but‐3‐yn‐2‐ols to functionaly embellished 2‐iodocarbazoles is described for the first time using iodine at room temperature in an open flask. This reaction proceeds through a cascade of 5‐ endo spirocyclization, ring‐rearrangement through a vinyl shift, and aromatization in a short time. This protocol offers direct access to uncovered 2‐iodocarbazoles, with a broad substrate scope and good to moderate yields. Further, we have demonstrated the synthetic potential of these compounds using cross‐coupling reactions. Abstract : A first approach to 2‐iodocarbazoles by benzannulation of indole‐tethered propargyl alcohols has been developed at room temperature in an open‐flask reaction using iodine. This benzannulation protocol involves a regioselective 5‐ endo ‐spirocyclization followed by a selective 1, 2‐alkenyl migration and aromatization cascade.